1997
DOI: 10.1099/00221287-143-7-2305
|View full text |Cite
|
Sign up to set email alerts
|

The starvation-stress response of Vibrio (Listoneila) anguillarum

Abstract: The starvation-stress response of Vibrio (Listonella) anguillarum was investigated and characterized with regard to changes in cell morphology and the ability of V. anguillarum to survive starvation, heat shock, exposure to H,O, and exposure to ethanol. The ability of V. anguillarum to survive exposure to the latter three stresses after initiation of starvation was also examined. Results of these experiments indicated that when starved for carbon, nitrogen and phosphorus, the c.f.u. of V. anguillarum declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In repeat experiments similar patterns were observed (data not shown), indicating that starvation does not provide cross-protection to hydrogen peroxide stress in a similar way to that observed in bacteria including E. coli (33), Pseudomonas putida (29), V. angustum S14 (34,46), Vibrio sp. strain Ant300 (54) and V. anguillarum (42). With the exception of cells which had just been starved, all cultures exhibited similar levels of stress resistance and remained more than 1% viable after a 60-min exposure to 20% ethanol (Fig 2C).…”
Section: Resultsmentioning
confidence: 85%
“…In repeat experiments similar patterns were observed (data not shown), indicating that starvation does not provide cross-protection to hydrogen peroxide stress in a similar way to that observed in bacteria including E. coli (33), Pseudomonas putida (29), V. angustum S14 (34,46), Vibrio sp. strain Ant300 (54) and V. anguillarum (42). With the exception of cells which had just been starved, all cultures exhibited similar levels of stress resistance and remained more than 1% viable after a 60-min exposure to 20% ethanol (Fig 2C).…”
Section: Resultsmentioning
confidence: 85%
“…In response to starvation or stress, S. maltophilia in tap water reduces the energy cost of chemotaxis by forming UMC (0.1 to 0.2 m) that can pass through a 0.2-m filter (316). UMC are formed in water (potable water, mineral water, and reverse osmosis water) by several genera of bacteria, including Stenotrophomonas, Pandoraea, Microbacterium, Afipia, Pseudomonas, Vibrio, Sphingomonas, and Aeromonas (95,145,164,209,221,241,316). It has been reported that biofilm and UMC can pass through these filter units, demonstrating that filtration has limited efficacy for the removal of these potential pathogens from water (316).…”
Section: Surfaces and Solutionsmentioning
confidence: 99%
“…Unpublished rpoS sequences have been submitted for another fish pathogen, Vibrio harveyi (accession number AF321124), but the role of RpoS in this organism and the factors that induce its expression are unknown. Nelson et al (36) concluded that the starvation stress response in V. anguillarum was different from that of other bacterial species since starvation caused only a temporal increase in resistance to other stress factors, such as ethanol exposure. Our finding that rpoS is present indicates that the response of V. anguillarum may not be very The A15 RAP-PCR clone has significant homology on the amino acid level to the corresponding vibE and entE genes of V. cholerae and E. coli, respectively.…”
Section: Discussionmentioning
confidence: 99%